2005
DOI: 10.1177/089686080502503s14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patient Flow into Dialysis: Role of Education in Choice of Dialysis Modality

Abstract: ♦ Background Despite advances in predialysis care, morbidity and mortality remain high. ♦ Objectives To analyze end-stage renal disease (ESRD) patient demographics and clinical data on education on dialysis treatment options, type of chronic renal replacement therapy (RRT), and effects of planned versus non-planned dialysis start. ♦ Methods 621 patients, from 24 Spanish hospitals, who started RRT in 2002. Peritoneal or vascular access at dialysis initiation was considered “planned.” ♦ Results 304 (49%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 8 publications
4
78
0
2
Order By: Relevance
“…The quality and quantity of pre-dialysis education and the level of support, in the form of a team of specialist nurses, do tend to influence the number of patients choosing a home modality. 13,14 Attending an options class pre-dialysis has been associated with more frequent selection of home dialysis, fewer tunneled HD catheters, and lower mortality risk during the first 90 days of dialysis therapy. 15 The impact of in-hospital pre-dialysis edu-cation program has also been positive on unplanned dialysis starts resulting in increased uptake of home dialysis therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and quantity of pre-dialysis education and the level of support, in the form of a team of specialist nurses, do tend to influence the number of patients choosing a home modality. 13,14 Attending an options class pre-dialysis has been associated with more frequent selection of home dialysis, fewer tunneled HD catheters, and lower mortality risk during the first 90 days of dialysis therapy. 15 The impact of in-hospital pre-dialysis edu-cation program has also been positive on unplanned dialysis starts resulting in increased uptake of home dialysis therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of patients across Europe start dialysis without permanent vascular access or a peritoneal dialysis (PD) catheter (Lorenzo et al 2004;Marron et al 2005;Aslam et al 2006;Mendelssohn et al 2011). The STARRT study (Study To Assess Renal Replacement Therapy) showed that out of 339 patients on dialysis, only 134 had received a planned start whilst 205 had received a suboptimal start (Mendelssohn et al 2011).…”
Section: Incidence Causes and Consequences (Morbidity Mortality Andmentioning
confidence: 99%
“…The STARRT study (Study To Assess Renal Replacement Therapy) showed that out of 339 patients on dialysis, only 134 had received a planned start whilst 205 had received a suboptimal start (Mendelssohn et al 2011). Numerous studies have shown that unplanned/suboptimal dialysis is associated with late referral (referral to a renal unit less than three months before start of dialysis) (Astor et al 2005;Lee et al 2005;Marron et al 2005;Ortega et al 2005;Aslam et al 2006) and often with the need for urgent dialysis (Astor et al 2001(Astor et al , 2005.…”
Section: Incidence Causes and Consequences (Morbidity Mortality Andmentioning
confidence: 99%
See 2 more Smart Citations